Efficacy of armodafinil on reducing excessive sleepiness in patients with shift work disorder: a systematic review and meta-analysis - José Pedro Teixeira Correia (2022)
Study Objectives: To conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) comparing the efficacy of armodafinil vs modafinil and/or placebo on reducing Shift Work Disorder (SWD) excessive sleepiness. Methods: PRISMA2020 recommendations were followed. Electronic databases PubMed, Web of Science, Scopus, ClinicalTrials.gov, EU Clinical Trials Register, CENTRAL and grey literature were searched for RCTs, published up to 19th March 2022. The primary endpoint was objective sleepiness, measured by Multiple Sleep Latency Test (MSLT). Secondary endpoints included subjective sleepiness, memory, reaction time, quality of life and adverse effects. Results: Six studies were included assessing a total of 871 participants. Compared to placebo, armodafinil 150-mg significantly improves objective sleepiness in patients with SWD (95% confidence interval [CI] = 1.83 to 7.17, P < 0.001), reduces subjective sleepiness (95%CI = -1.29 to -0.66, P < 0.00001), enhances reaction time (95%CI = -84.91 to -20.31, P = 0.001), improves memory and quality of life. However, it increases the risk of developing headache (95%CI= 0.99 to 2.82; P = 0.05), nausea (95%CI = 1.32 to 5.11; P = 0.006) and anxiety symptoms (95%CI = 1.06 to 9.72; P = 0.04). Armodafinil 150-mg and modafinil 200-mg have comparable safety profiles and similar efficacy in reducing subjective sleepiness. Conclusion: Armodafinil 150-mg is a safe option for reducing excessive sleepiness in patients with SWD. Nevertheless, further wide-scale and adequately powered trials are still needed to investigate whether armodafinil is a better option than modafinil.